Diagnóstico y tratamiento de la apnea-hipoapnea obstructiva del sueño con aparatología intra-oral. Revisión sistemática de la literatura (2021)
Obstructive sleep apnea-hypopnea syndrome is a frequent disorder in the population worldwide. The most common characteristics in this disorder were snoring, excessive daytime sleepiness, and apneic events. The most reported predisposing factors are comorbidities, obesity, diseases, syndromes, and anatomical considerations. Some alterations that were found are oral respiration, alterations in the bite, and retracted jaw. Finally, it was determined that the appliances with the greatest predilection for the treatment of OSAHS are mandibular repositioning appliances.